A comparative study of manipulator teleoperation methods for debris retrieval phase in nuclear power plant decommissioning. (3rd May 2023) - Mizuno, Naoki; Tazaki, Yuichi; Hashimoto, Tatsuya; Yokokohji, Yasuyoshi
ABSTRACT: This paper presents a comparative study of teleoperation methods of robotic manipulators aiming at application to the decommissioning operation of the primary containment vessel (PCV) of Fukushima Daiichi Nuclear Power Plant Unit 3. A detailed set of mockup is constructed from data collected by internal investigation of the damaged PCV, and a series of teleoperation experiments using a dual-arm robotic manipulator simulating the actual obstacle removal operation is conducted. Three teleoperation methods, manual, teaching-based, and planning-based, are compared in terms of multiple performance indices. The manual teleoperation resulted in low efficiency and safety, and high cognitive load. The method based on pre-recorded teaching data showed the highest safety score, but required large amount of time for preparation. The planning-based method achieved efficient teleoperation with small amount of preparation time, while it was found that it needs further improvement in terms of safety. GRAPHICAL ABSTRACT: UF0001